Growth performance and immunological and antioxidant status of Chinese shrimp, Fennerpenaeus chinensis reared in bio-floc culture system using probiotics. Issue 1 (November 2015) - Kim, Min-Su; Min, EunYoung; Kim, Jun-Hwan; Koo, Ja-Keun; Kang, Ju-Chan
Abstract: Chinese shrimp Fennerpenaeus chinensis (mean length 1.86 ± 0.15 cm, and weight 137.4 ± 12.7 mg) were reared in the different concentrations of bio-floc (control, 60, 80, 100, 120, and 140%) for 90 days. The growth rate was significantly increased over 100% bio-floc concentrations. In the immunological parameters, the gene expression of proPO and lysozyme was considerably increased over 120% bio-floc concentrations. The gene expression of SP was notably elevated at 140% bio-floc concentration. In the antioxidant enzymes, the activity of SOD was considerably decreased over 80% bio-floc concentrations. A notable decline in the activity of CAT was observed over 120% bio-floc concentrations. The results indicate that rearing of Chinese shrimp in bio-floc system can induce the increase of growth performance, enhancement of immune responses, and reduction of oxidative stress. Highlights: The growth performance was significantly increased in bio-floc system using EM. The immune responses were stimulated in bio-floc system using EM. The antioxidant enzymes were considerably decreased in bio-floc system using EM.